Shielded metal arc welding of UNS S32750 steel: microstructure, mechanical properties and corrosion behaviour. (22nd August 2018) - Dandekar, Tushar Ramdas; Gupta, Aman; Kumar, Amit; Khatirkar, Rajesh Kisni; Vadavadagi, Basavaraj
Abstract: In the present investigation, ER2594 (conventional) and ER2595 (consisting of additional Cu and W) electrodes were used to produce butt joints of 5.5 mm thick super duplex stainless steel (UNS S32750) sheets using shielded metal arc welding (SMAW) process. During SMAW process, the heat input was 0.81 kJ mm −1 for ER2594 electrode and 0.75 kJ mm −1 for ER2595 electrode. Optical microscope and scanning electron microscope were used to observe the microstructures of different zones, namely, fusion zone (FZ), heat affected zone (HAZ) and base metal (BM). Tensile test, impact test and micro-hardness measurements were carried out for both the weldments on samples cut across the weld. The microstructures of the FZ consisted of inter-granular austenite (IGA), grain boundary austenite (GBA) and Widmanstatten austenite (WA). There was minor change in the width of the HAZ of the weldments with the change in electrode. This is expected to be due to the minor change in the heat input during SMAW process. The weld zone (cap pass) of both the weldments predominantly showed WA and mode of solidification was found to be ferritic (F mode). The tensile strength of both the weldments was approximately same as that of base metal and both the samples fractured through the BM. Cr, Fe and Mo rich precipitates were found in the FZ (weld region), which are expected to be formed due to pick of gaseous content from the atmosphere during welding. The FZ of the weldments produced by ER2595 electrode showed better pitting corrosion resistance than those produced by ER2594 electrode.